Effect of digital ocular massage on intraocular pressure and Schlemm’s canal dimensions - Wu, Tiffany H. Y.; Lau, Henry K. C.; Lai, Carmelo H. Y.; Wong, Ruby W. L.; Wong, Antonia K. W.; Lam, Andrew Kwok-cheung (Scientific reports, 2024)
Digital ocular massage has been reported to temporarily lower intraocular pressure (IOP). This could be related to an enhanced aqueous humor outflow; however, the mechanism is not clearly understood. Using anterior segment optical coherence tomography, the Schlemm’s canal (SC) and trabecular meshwork (TM) can be imaged and measured. Here, 66 healthy adults underwent digital ocular massage for 10 min in their right eyes. The IOP and dimensions of the SC and TM were measured before and after ocular massage. All subjects demonstrated IOP reduction from 15.7 ± 2.5 mmHg at baseline to 9.6 ± 2.2 mmHg immediately after, and median of 11.6 mmHg 5-min after ocular massage (Friedman’s test, p < 0.001). There was significant change in SC area (median 10,063.5 μm 2 at baseline to median 10,151.0 μm 2 after ocular massage, Wilcoxon test, p = 0.02), and TM thickness (median 149.8 μm at baseline to 144.6 ± 25.3 μm after ocular massage, Wilcoxon test, p = 0.036). One-third of the subjects demonstrated collapse of the SC area (−2 to −52%), while two-thirds showed expansion of the SC area (2 to 168%). There were no significant changes in SC diameter (270.4 ± 84.1 μm vs. 276.5 ± 68.7 μm, paired t -test, p = 0.499), and TM width (733.3 ± 110.1 μm vs. 733.5 ± 111.6 μm, paired t -test, p = 0.988). Eyes with a higher baseline IOP demonstrated a greater IOP reduction (Pearson correlation coefficient r = −0.521, p < 0.001). Eyes with smaller SC area at baseline showed greater SC area expansion (Pearson correlation coefficient = −0.389, p < 0.001). Greater IOP reduction appeared in eyes with greater SC area expansion (Pearson correlation coefficient r = −0.306, p = 0.01). Association between change in IOP and change in TM thickness was not significant (Spearman’s ρ = 0.015, p = 0.902). Simple digital ocular massage is an effective method to lower IOP values, and change in the SC area was significantly associated with IOP changes.